Pengaruh Ambiguitas Peran dan Kepuasan Kerja terhadap Kinerja Karyawan pada Bank 9 Jambi Cabang Muara Bulian - Satya Wahyudi; Neng Setiawati (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this research to determinate the effect of role ambiguity and job satisfaction on employee performance at Bank 9 Jambi Branch of Muara Bulian. The sample on this research is consist of done by using the method of judgement sampling is by taking a sample selected by as much as 41 respondent on Bank ( Jambi Branch of Muara Bulian and analyzed using multiple linear regression with the help of Statistical Product and Service Solution (SPSS) version 20.0. The result of this research is Y = 1,539 + 0,330. X1+ 0,491. X2. This showed that role ambiguity and job satisfaction has a positive effect and significant to employee performance.